A comparative study of some physical and skill traits according to the playing centers of basketball players -A field study for the U15 Oum El Bouaghi basketball team - نواصرية , منى (sports creativity, 2025)
The study aimed to identify the differences between physical and skill traits in basketball according to playing positions, and the study sample consisted of U15 basketball players of the ASSOB team for oum el-Bouaghi, and the latter was chosen deliberately, and the researcher relied on the relational descriptive approach for its relevance to the nature of his research. The researcher used the physical tests (Sargent test and the translational velocity test) and skill (aiming skill test) related to the study, and the researcher reached the following: There were statistical differences in some attributes and occupations according to playing positions in basketball.